A review on different Nano-Enhanced techniques for productivity improvement of solar stills - Cakmak, Fethi Ahmet; Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2024)
Water distillation systems are becoming more and more important as the world's supplies of clean water are running out. Distillation systems powered by solar energy, a renewable and clean energy source, are used in places where it is difficult to access clean water. Due to the low efficiency of traditional solar distillation systems, many active and passive studies are being carried out to improve these systems. The use of nanoparticles to increase thermal conductivity in distillers is one of the frequently used passive methods. In distillers, nanoparticles can be used in the base insulation, on the bottom absorber surface, on the condenser surface and as nanofluid in the water to be distilled. In this study, the use of nanoparticles in almost all forms in solar distillers was examined by comparing the results available in the literature by using results from different numerical and experimental studies. Comparisons are made and potential of using nano-powders in solar stills on the performance improvement are assessed. When the results are examined, it can be seen that by using nanoparticles with phase change materials in the base insulation, an efficiency increase of 10%-200% compared to the traditional distiller could be achieved. By using nanoparticles on the bottom absorber surface, an efficiency increase of nearly 100% compared to the traditional distiller could be achieved. By using them on the condenser surface, an efficiency increase of nearly 30% could be achieved. Finally, by using them as nanofluid in the liquid to be distilled, an efficiency increase of 10%-300% compared to the traditional distiller could be achieved. Some technical challenges and suggestions for futher applications of nanopowders in solar stills are provided.
Keywords: Solar still; Nano materials; Energy storage materials; Nanofluid